2021
DOI: 10.1039/d1qm00313e
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-enhanced emission in tetraphenylpyrazine-based luminogens: theoretical modulation and experimental validation

Abstract: The AEE properties of TPP-based luminogens can be modulated via the following guideline: the phenyl attachment reduces the n → π* transition component and evokes RIM, while the substituent decoration imparts altered electronic conjugation and promotes RIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The prior analysis on the total λ e suggests that k nr of the TPP derivatives would be much slower than that for the single TPP (2.9 × 10 11 ) reported in our previous work. 7 The energy gap law tells us that a small Δ E ad favors a fast k nr . This is because log ( k nr ) decreases almost linearly with Δ E when Δ E is large enough.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prior analysis on the total λ e suggests that k nr of the TPP derivatives would be much slower than that for the single TPP (2.9 × 10 11 ) reported in our previous work. 7 The energy gap law tells us that a small Δ E ad favors a fast k nr . This is because log ( k nr ) decreases almost linearly with Δ E when Δ E is large enough.…”
Section: Resultsmentioning
confidence: 99%
“…4–6 Recently, we investigated the AEE mechanism of TPP-based luminogens in theory. 7 It was found that the restricted rotations of the four peripheral phenyls attached to the pyrazine core are responsible for the AEE characteristics. In experiments, enthusiastic efforts have been devoted to develop TPP derivatives with desired luminescent properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al used QM/MM methods to investigate the structure and stability of vanadium-doped active sites in Al-MCM-41, and their potential use as heterogeneous catalysts for the oxidation of furans. 210 Besides catalysis applications, covalent QM/MM embedding methods in ChemShell have also been recently applied to the excited state properties of organic materials [211][212][213][214][215][216] and the adsorption of hydrogen onto amorphous solid water. 217 The ionic QM/MM embedded cluster approach can be used to model both bulk defects and surface reactivity.…”
Section: Solid State Embeddingmentioning
confidence: 99%
“…Their unique optical properties make them promising candidates for these applications. Overall, AIEgens are a promising alternative to traditional fluorophores, and their unique properties make them useful for a variety of applications in biotechnology, materials science, and optoelectronics [ 64 , 65 , 66 , 67 ].…”
Section: Fret Description Detailsmentioning
confidence: 99%